Women's health nursing in traditional and complementary medicine practices - CAN GÜRKAN, ÖZLEM (My University, 2022)
Women’s health is the state of complete physical, psychological, social, and cultural wellbeing. Specific nursing practices for women’s health require dynamic and highly autonomous roles that require expert knowledge in order to evaluate, diagnose, and treat actual and potential health problems of individuals, families, and societies. Today, traditional and complementary medicine is practiced in this field by various methods such as acupuncture, homeopathy, ayurveda, massage, reflexology, hypnosis, aromatherapy, yoga, meditation, reiki, therapeutic touch therapy, music therapy, and dance therapy. It is seen that women’s health nurses play an active role in a wide range of these practices. In this review, the role of women’s health nurses in traditional and complementary medicine practices at the international level is discussed with legal frameworks.
Keywords: Women’s health is the state of complete physical; psychological; social; and cultural wellbeing. Specific nursing practices for women’s health require dynamic and highly autonomous roles that require expert knowledge in order to evaluate; diagnose; and treat actual and potential health problems of individuals; families; and societies. Today; traditional and complementary medicine is practiced in this field by various methods such as acupuncture; homeopathy; ayurveda; massage; reflexology; hypnosis; aromatherapy; yoga; meditation; reiki; therapeutic touch therapy; music therapy; and dance therapy. It is seen that women’s health nurses play an active role in a wide range of these practices. In this review; the role of women’s health nurses in traditional and complementary medicine practices at the international level is discussed with legal frameworks.